The ghost women : a novel - Murphy, Jennifer, 1956 February 14- (Dutton, 2026)
"A mysterious art academy in the woods, a deck of ancient tarot cards, a centuries-old secret. On a hot August morning in 1972, the body of Abel Montague, a student at St. Luke's Institute of the Arts, is found hanging from a tree in the forest. An ancient Hanged Man tarot card is found in the back pocket of his pants and his body has been positioned into the exact pose illustrated on the card. When Detective Lola Germany arrives at St. Luke's-a former monastery that once housed a secret order of monks who carried out witch trials and executions-she believes they are dealing with a ritualistic murder. While interviewing school administrators and Abel's classmates, Lola discovers Abel's live-in girlfriend, Pearl, seems shaken but also might be hiding something-along with her group of friends who call themselves witches. When more students are found dead, each body arranged like a tarot card, Lola realizes she is trapped in a web of power and ambition that spans centuries. Soon the lines between past and present, spiritual and tangible, begin to blur, and the only way to survive is to seek answers from places she never imagined"-- Provided by publisher.